(untitled) (Spandan, 2024)
This study explores how poetry from grade 10 English textbook in Nepal can be utilized to enhance key soft skills for the 21st century in students. This study employed a textual analysis of selected poems of grade 10 and found the avenues for cultivating soft skills such as communication, collaboration, critical thinking, creativity, leadership, empathy, adaptability and emotional intelligence. Despite the lack of explicit texts and tasks targeting these soft skills in the textbook, the poems’ composition and thematic content, and pedagogical strategies such as discussions, role-playing, reflective presentations, and group work enhance the students’ cognitive, emotional, and ethical growth resulting in cultivating soft skills. Furthermore, the study highlights that the poetry and poetry-based pedagogy into ELT classrooms can simultaneously enhance the linguistic proficiency and soft skills as well as provide the insights for curriculum designing, textbook writing and effective classroom teaching.